THE INFLUENCE OF SEASON ON THE QUALITY INDICATORS AND FATTY ACID COMPOSITION OF COW’S MILK - Pavkovych С.; Vovk С.; Ohorodnyk Н.; Dudar І.; Tkachuk В.; Kozak Р.; Ratskyi М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
This article presents the results of research on the impact of the indoor and grazing periods on the quality indicators and fatty acid composition of cow's milk. Milk is characterized by its high nutritional value, as it contains an optimal amount of proteins, fats, carbohydrates, minerals and vitamins. However, milk from the grazing and indoor periods differs in its component content and fatty acid composition. Therefore, the research aimed to compare the quality indicators and fatty acid composition of milk obtained during the indoor and grazing periods. The study was conducted during both the indoor and grazing periods on cows of the Ukrainian black-and-white dairy breed. During the indoor period, the animals were fed a diet comprising clover hay, corn silage, lucerne silage, compound feed, and mineral supplements. In contrast, during the grazing period, their diet included green forage from cereal-legume crops, as well as compound feed and mineral supplements. Both diets were meticulously balanced for energy and nutrients. Milk samples were collected bi-monthly at regular intervals throughout the indoor period (November to March) and the grazing period (May to September). The results showed that milk from cows during the indoor period contained higher levels of fat and protein, while the lactose content was lower compared to milk obtained during the grazing period. The dry matter and dry non-fat solids content were also higher in milk from cows during the indoor period. Milk from cows obtained in different seasons also differed in fatty acid composition. Milk from cows during the grazing period contained lower amounts of lauric, myristic and palmitic acids, but higher amounts of stearic, oleic, linoleic and linolenic acids compared to milk from the indoor period. Milk from the grazing period had a lower total content of medium-chain fatty acids (C12–C16) and a higher content of long-chain fatty acids (C18). The amount of saturated fatty acids was higher in milk from cows during the indoor period, while the amount of unsaturated and polyunsaturated fatty acids was higher in milk from cows during the grazing period. The ratio of monounsaturated to saturated and polyunsaturated to saturated fatty acids was higher in milk from cows during the grazing period.